Dampak Supplier Relationship Management Atas Kinerja Ekspor (Studi Kasus PT Pundi Alam Perkasa) - Muhammad Fakhrizal Amri; Christine Widilestari; Lia Retian Asfirah (PPPM Polimarin, 2025)
PT Pundi Alam Perkasa is a company operating in the woodworking industry, with a primary focus on the export market and producing barecore products. This study identified that the company experienced a decline in the supply of wood raw materials during a certain period, while export activities continued to run smoothly. This phenomenon became the basis for conducting a more in-depth study to examine the possible influence of supplier relationship management on the availability of raw materials, which affects the smooth running of the production process. The purpose of this study is to analyse the effect of Supplier Relationship Management (SRM) implementation on the export performance of PT Pundi Alam Perkasa, as well as to examine the strategies applied by the company in dealing with raw material supply constraints. The research approach used is a mixed methods approach with an Exploratory Sequential Design. The findings show that SRM has a positive effect on the company's export performance. Strong and effective relationships with suppliers contribute to improved product quality, increased operational efficiency, and the company's ability to meet international market demand. The strategies implemented to overcome raw material supply shortages include: adjusting or increasing the price of wood raw materials, continuing the production process by making adjustments, and seeking alternative raw material suppliers.